Right Upper Lobe Partial Anomalous Pulmonary Venous Connection. (16th February 2014) - Tourmousoglou, Christos; Kalogeropoulou, Christina; Koletsis, Efstratios; Charoulis, Nikolaos; Prokakis, Christos; Alexopoulos, Panagiotis; Margaritis, Emmanoil; Dougenis, Dimitrios
Abstract : Partial anomalous pulmonary venous return (PAPVR) is a left-to-right shunt where one or more, but not all, pulmonary veins drain into a systemic vein or the right atrium. We report a case of a 45-year-old male with PAPVR to superior vena cava which was incidentally discovered during a right lower bilobectomy for lung cancer.